Proteomimetics of Natural Regulators of JAK–STAT Pathway: Novel Therapeutic Perspectives - La Manna, Sara; De Benedictis, Ilaria; Marasco, Daniela (Frontiers in Molecular Biosciences, 2022)
The JAK)-STAT pathway is a crucial cellular signaling cascade, including an intricated network of protein-protein interactions (PPIs) responsible of its regulation. It mediates the activities of several cytokines, interferons and growth factors and transduces extracellular signals into transcriptional programs to regulate cell growth and differentiation. It is essential for the development and function of both innate and adaptive immunity and its aberrant deregulation was highlighted in neuroinflammatory diseases and in crucial mechanisms for tumor cell recognition and tumor-induced immune escape. For its involvement in a multitude of biological processes, it can be considered as a valuable target for the development of drugs even if a specific focus on possible side effects associated with its inhibition is required. Herein we review on the possibilities to target JAK-STAT by focusing on its natural inhibitors as the suppressor of cytokine signaling (SOCS) proteins. This protein family is a crucial checkpoint inhibitor in immune homeostasis and a valuable target in immunotherapeutic approaches to cancer and immune deficiency disorders.